2022
DOI: 10.17770/sie2022vol1.6835
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of a Dance Lesson for Promotion of Well-Being of Adults

Abstract: The context of the Covid-19 pandemic has highlighted the idea of improving the quality of life and health of people in the context of modern research. If a person is satisfied with himself, has self-realized, with a good physical well-being, he feels satisfied with life in general, thus promoting a quality of life for himself. There is an ageism perception in society that dance classes are suitable for young people. However, when forms of artistic expression are used to promote well-being in adults, it gains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It provides emotional relief, helps to concentrate, and can be used as a form of psychological relief (Collard-Stokes & Yoon, 2022). Dance also improves physical and mental health and wellbeing through creative expression, movement, and social connections (Zīsberga, 2022). It promotes self-realization, self-efficacy, positivity, and self-awareness, contributing to overall well-being and healthy aging.…”
Section: Introductionmentioning
confidence: 99%
“…It provides emotional relief, helps to concentrate, and can be used as a form of psychological relief (Collard-Stokes & Yoon, 2022). Dance also improves physical and mental health and wellbeing through creative expression, movement, and social connections (Zīsberga, 2022). It promotes self-realization, self-efficacy, positivity, and self-awareness, contributing to overall well-being and healthy aging.…”
Section: Introductionmentioning
confidence: 99%
“…Well-being is a sustainable condition that allows a person to live and develop qualitatively. Therefore, in many sectors, well-being in theoretical concepts becomes the subject of research (Zīsberga, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this publication is to identify the components of well-being formation in an adult dance class from the teacher's point of view. Such a choice of focus was determined by the results of the previous research stage (Zīsberga, 2022), where one of the criteria of well-being was identified in the dancers' interviews: the personality and professional mastery of the teacher, as well as the still current idea that the vital aspect of art pedagogy is how the teacher conceptualizes the pedagogical process. At this stage of the research, it was concluded that a dance teacher is an essential component in promoting dancers' well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Well-being is a sustainable condition that allows a person to live and develop qualitatively. Therefore, in many sectors, well-being in theoretical concepts becomes the subject of research (Zīsberga, 2022).…”
Section: Introductionmentioning
confidence: 99%